Odpowiedzi

Najlepsza Odpowiedź!
2010-02-24T19:21:21+01:00
A) 5(x+2)-3(-2x+1)=5x+10+6x-1=11x+9

b) 3(2x-3)-5(-3x+1)+5(-x+5)=6x-9+15x-5-5x+25=14x-14

c) 3x(x+2)-5(x²+3)= 3x²+6x-5x²-15=-2x²+6x-15
1 5 1
2010-02-24T19:22:17+01:00
A) 5(x+2)-3(-2x+1)= 5x+10+6x-3 = 11x+7

b) 3(2x-3)-5(-3x+1)+5(-x+5)= 6x-9+15x-5-5x+25 = 16x+11

c) 3x(x+2)-5(x²+3)= 3x²+6x-5x²-15 = -2x²-9
1 5 1
2010-02-24T19:24:23+01:00
A) 5(x+2)-3(-2x+1)=5x+10+6x-3=11x+7
b)3(2x-3)-5(-3x+1)+5(-x+5)=6x-9+15x-5-5x+25=16x-39
c)3x(x+2)-5(x²+3)=3x²+6x-5x²-15=-2x²+6x-15
1 5 1